Combined use of LC–ESI-MS and antifungal tests for rapid identification of bioactive lipopeptides produced by Bacillus amyloliquefaciens CCMI 1051 - Caldeira, A. Teresa (2011)
The strain Bacillus amyloliquefaciens CCMI 1051 used in this study has been isolated in our laboratory from healthy Quercus suber in the south of Portugal and shows high levels of antagonistic properties against filamentous fungi that attack forest products industry due to the production of bioactive peptides. A combined use of LC–ESI-MS and antifungal tests allowed a rapid identification of lipopeptides as active compounds produced. Applying autobiographic methods it was possible to obtain active compounds. LC–ESI-MS, a powerful tool for rapid identification, indicates the presence of lipopeptides and MS2 electrospray ionization showed the partial sequence Tyr–Asn–Pro–Glu in the peptidic portion of some compounds produced. The association of mass spectrometry and chromatography, used in parallel with antifungal tests proved to be an efficient approach for the characterization of active lipopeptides without the need of previous total isolation. This methodology can be employed for screening and optimization the production of antifungal iturinic lipopeptides, showing a great potential for future application.